СAN TREES HELP REDUCE LEAD IN URBAN AIR? А CASE STUDY OF GREENING IN A RUSSIAN INDUSTRIAL CITY - Krupnova, Tatyana; Rakova, Olga; Berentseva, Susanna; Gavrilkina, Svetlana; Udachin, Valerii (GEOMATE Journal, 2022)
Urban trees can be effectively used as a biomonitor and phytoremediator of air pollution, but not all species are equally capable of filtering the air. Lead-containing PM2.5 has raised severe public health concerns in industrial cities. PM2.5 pollution episodes occur in Chelyabinsk (Russia) because of a zinc production plant located in the urban area. During zinc production from lead-zinc concentrates, the environment around the enterprise may become contaminated with lead. We measured the amount of Pb in PM2.5 and Pb accumulated by the leaves of Betula pubescens, Populus nigra L., Acer negundo L. and Pinus silvestris L. from the 32 sites. The lowest value of Spearman’s coefficient was found for pine needles. The stomata of the needles were clogged with anti-icing agents that had accumulated over the winter. Pb found in the tree leaves correlated significantly with that found in the PM2.5. The correlations of Pb concentration were maximal for birch tree leaves. The leaves of all three species studied − B. pubescens, P. nigra, A. negundo − can be used as phytoremediators of Pb air pollution in the Chelyabinsk urban area.